ADHD and Bipolar Disorder Subtype - J Gordon Millichap (Pediatric Neurology Briefs)
A familial relationship between attention-deficit hyperactivity disorder (ADHD) and bipolar disorder (BPD) was examined in 140 children with ADHD, 120 non-ADHD controls, and their 822 first-degree relatives by analyses of structured psychiatric interviews at the Pediatric Psychopharmacology Unit, Massachusetts General Hospital, Harvard Medical School, Boston, MA.